Regionaal beleid in het herstructureringsgebied - J. H. M. Wilbers (Netherlands Journal of Geosciences, 1971)
In this paper the problems related to the restructuring policy in Southern Limburg (including that part of the middle of Limburg eastward of the Meuse river) are discussed. In mid 1965 the mining industry employed 45,000 men which represented 50% of the industrial population. The total number of male employables in the area of restructuring defined above amounted to 186,000 in late 1965 and is expected to reach 190,000 by the end of 1975 and 228,500 by the end of 1985. How these figures are arrived at is discussed in detail and it is concluded that new employment opportunities to be created during the period 1960-1975 amount to 49,400 and to 39,300 for the period 1916-1985. The author claims that initially far too much attention has been given to employment opportunities in industry and not to service and other peripheral activities. Since 1965 more than 30,000 mining jobs have disappeared. From 1966 till 1971 86 new industrial projects have been created with a forecasted number of 17,000 jobs, of which 61 projects of 8,000 jobs have been realized. Already existing industry grew by 2,800 jobs. Since the end of 1969 growth has been stagnent, mainly due to emigration from Limburg, the early pensioning of miners, the employment of handicapped miners in social schemes and the commuting the highly paid employment in labour - short Germany. Furthermore the active recruiting by Belgian industries and the personnel policies followed by the mining concerns have aggravated this situation. Even during the present boom, results of restructuring have fallen off and if a mild depression were to occur, trouble on the employment side might be expected. According to the author the limited restructuring policy has to be reshaped on a much broader regional basis. With a new and more imaginative policy we should also want improved labour mediation, a systematic reschooling policy, a larger and more flexible employment potential and a more selective investment policy. Improved economical, social and fiscal policies are feasible for the benefit of Limburg. It will serve no purpose to hold the proposed new policy pending the complete integration and harmonization within the European Economic Community. With relatively minor direct Governmental involvement much can be accomplished in the outlying regions of the Netherlands.